Records Management Procedures at PT. Bank Sumut Syariah Medan Branch Office - Meliyani Meliyani; Muhammad Lathief Ilhamy Nasution (Penerbit Jurnal Indonesia, 2022)
This study describes the file management procedures at PT. Bank Sumut Syariah Medan Branch. The purpose of this study is (1) to describe how the records management system at PT. Bank Sumut Syariah Medan Branch; (2) describe some of the obstacles faced by PT. Bank Sumut Syariah Medan Branch in archive management; (3) describe the steps taken to prevent problems in the archive management process at PT. Bank Sumut Syariah Medan Branch. Data was collected through observation and interviews. Based on the results of the study, it can be concluded: First, archive management is still not done well, in terms of inefficient storage processes. Second, the limitations encountered in records management procedures, namely: (1) inappropriate storage procedures; (2) archive storage and maintenance infrastructure is not optimal; (3) the absence of professional archivists. Third, efforts are being made to prevent records management problems, namely: (1) improving the storage procedures used; (2) optimization of storage space infrastructure and archive maintenance; (3) provide professional archiving staff.